THE INFLUENCE OF MATERIALISM TOWARDS CHARACTERS DEVELOPMENT IN F. SCOTT FITZGERALD’S THE GREAT GATSBY - Sekar Setyaning Arum; eko budi setiawan (Humaniora Scientia, 2019)
The objectives of this study entitled The Influence of Materialism Towards Characters Development in F. Scott Fitzgerald’s The Great Gatsby are (1) to figure out the materialism described through the character of Jay Gatsby and Daisy Buchanan. (2) to learn the influence of materialism towards the characters development of Jay Gatsby and Daisy Buchanan. The writer used library research to analyze the analysis. The main data is taken from novel of The Great Gatsby. Some theories used to analyze the data are American Dream, Character, Character Development, Marxism, and Materialism. Moreover, the approaches used in this research are sociological approach, psychological approach, marxism approach. The portrait of materialism in The Great Gatsby can be seen through the main characters namely Jay Gatsby and Daisy Buchanan. Both of them represent materialism in two ways which relate to the wealth that they have and their effort in pursuing their American Dream. Furthermore, their materialistic lifestyle also influences their characters development. It makes their desire become unattainable and their efforts directed towards a negative outcome. Jay Gatsby suddenly is being so ambitious and being spendthrift along with the story. Besides, Daisy Buchanan is also being a careless and shallow person who sees nothing except money and material luxury. Keywords: American dream, materialism, character development